Augmented reality in biology education: A systematic literature review - Tutut Indria Permana; H. Husamah; Moh Irfan Nurhamdani; Alia Zaskia; Aulia Savitri; Diva Aulia Salsabila (Research and Development in Education (RaDEn), 2024)
Augmented Reality (AR) has seen extensive utilization in the modern era, driven by rapid technological advancements. The aim of the Systematic Literature Review (SLR) method is to meticulously analyze and assess previous research on a specific phenomenon in a systematic and explicit manner. The search was conducted on the Scopus database using the keyword "Augmented Reality," resulting in 209 relevant articles. Out of this total, 35 articles passed the journal selection criteria and were deemed ready for analysis. The article selection process was carried out using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) model for inclusion and exclusion purposes. Since 2019, there has been a rising trend in research on augmented reality. The issue of AR can be approached through quantitative, qualitative, mixed-methods, and even development research (R&D). The most prominent author in AR research is NF Saidin. The data shows that the keyword "augmented reality" is strongly associated with "education" and "biology." These keywords are linked to concepts such as teacher training, augmented reality tools, teaching, biology learning, learning performance, e-learning, and virtual reality. Themes related to AR in education focus on teacher training in biology, which applies e-learning or mobile learning based on AR and virtual reality (VR). Articles were published by authors from 28 different countries, with authors predominantly from Asia. There are 15 institutions worldwide that fund AR research and publications. It can be concluded that the focus on AR in biology education will continue to grow, supported by the ongoing emphasis on technology in the modern era. This trend is reflected in the distribution year, research types/methods, instruments, areas of study, authors, keywords, authors’ nationalities, and collaboration patterns.